2019
DOI: 10.3389/fpsyg.2019.01565
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Faith: The Influence of Athletes’ Coping Self-Efficacy on the Cognitive Processing of Psychological Stress

Abstract: Coping self-efficacy (CSE) has a positive mental health effect on athletes’ ability to cope with stress. To understand the mechanism underlying the potential impact of CSE, event-related potentials (ERPs) were used to explore the neural activity of the cerebral cortex under acute psychological stress in athletes with different CSE levels. Among 106 high-level athletes, 21 high-CSE athletes and 20 low-CSE athletes were selected to participate in the experiment. A mental arithmetic task was used to induce acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The study of Guo et al ( 24 ) examined differences between athletes with high and low coping self-efficacy (CSE) levels under acute psychological stress . The study showed that low-CSE athletes lacked confidence and hence were more likely to not know what to do when facing stress.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of Guo et al ( 24 ) examined differences between athletes with high and low coping self-efficacy (CSE) levels under acute psychological stress . The study showed that low-CSE athletes lacked confidence and hence were more likely to not know what to do when facing stress.…”
Section: Resultsmentioning
confidence: 99%
“…However, traditional sport psychology is mainly focused on optimizing performance in a presumably healthy population, although mental health problems in elite sport have received increased attention, revealing the need for a broader mental health continuum ( 42 , 73 ) and for more attention to the potential relationship of athletic coping skills with well-being and mental health ( 40 ). As coping self-efficacy has a positive mental health effect on athletes' ability to cope with stress, athletes can thus better cope with and eliminate interference caused by competitive stressors and eventually achieve their best performance and protect their mental health ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a feeling or belief that one can successfully deal with stressors like academic demands and family problems. The measure of coping self-efficacy has been used across ages and different situations, like in the study of Guo et al (2019), where the results indicate that athletes with high coping self-efficacy can better cope with stressful events, regulate their actions accordingly and move their attention to process positive information. Schneider's (2020) study among high school students showed a positive and significant relationship between strengths use and well-being, strengths use and coping self-efficacy, coping self-efficacy and well-being.…”
Section: Introductionmentioning
confidence: 99%